Immature Politicians and Oligarchy As a Threat to Democracy - Muhammad Zulfan Hakim; Fajlurrahman Jurdi (Fiat Justisia: Jurnal Ilmu Hukum, 2017)
The rise of oligarchy in political democracy in Indonesia has more potential to exterminate democracy in Indonesia itself. Democracy might be used as just a tool by the oligarchy. Oligarchy is the cause that some immature politicians with a very short experience are now holding vital positions such as regents, a party leader, or local parliament member. Some of them might have no integrity, and there is a big possibility that they only just a freeloader from their parents or family experience in politics.  Keywords: Political party, Oligarchy, Immature Politicians